Ultra-low loss quantum photonic circuits integrated with single quantum emitters - Chanana, Ashish; Larocque, Hugo; Moreira, Renan; Carolan, Jacques; Guha, Biswarup; Melo, Emerson G.; Anant, Vikas; Song, Jindong; Englund, Dirk; Blumenthal, Daniel J.; Srinivasan, Kartik; Davanco, Marcelo (Nature Publishing Group, 2022)
The scaling of many photonic quantum information processing systems is ultimately limited by the flux of quantum light throughout an integrated photonic circuit. Source brightness and waveguide loss set basic limits on the on-chip photon flux. While substantial progress has been made, separately, towards ultra-low loss chip-scale photonic circuits and high brightness single-photon sources, integration of these technologies has remained elusive. Here, we report the integration of a quantum emitter single-photon source with a wafer-scale, ultra-low loss silicon nitride photonic circuit. We demonstrate triggered and pure single-photon emission into a Si3N4 photonic circuit with approximate to 1dB/m propagation loss at a wavelength of approximate to 930nm. We also observe resonance fluorescence in the strong drive regime, showing promise towards coherent control of quantum emitters. These results are a step forward towards scaled chip-integrated photonic quantum information systems in which storing, time-demultiplexing or buffering of deterministically generated single-photons is critical. Applications of ultra-low-loss photonic circuitry in quantum photonics, in particular including triggered single photon sources, are rare. Here, the authors show how InAs quantum dot single photon sources can be integrated onto wafer-scale, CMOS compatible ultra-low loss silicon nitride photonic circuits.